2017
DOI: 10.4306/pi.2017.14.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing Disorders are Associated with Duration of Current Episode and Severity of Side Effects

Abstract: ObjectiveLonger duration of untreated illness, longer duration of current episode, and the severity of medication side effects may negatively impact on the perceived disability and psychosocial impairment of patients with major affective and anxiety disorders. Studies also suggested the involvement of sensory perception in emotional and psychopathological processes. The present study aimed to examine the relationship between Sensory Processing Disorders (SPD), duration of untreated illness and current illness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
2
11
0
1
Order By: Relevance
“…In contrast, a Sensation Seeking pattern on the AASP tends to correlate with more adaptive behaviour, such as higher positive affect (Engel-Yeger and Dunn, 2011a) and lower sleep disturbances (Engel-Yeger and Shochat, 2012). Correlates of SPP in healthy adults show continuity with similar studies in people with affective and anxiety disorders, which have shown that such disorders correspond with higher rates of Sensory Sensitivity, Sensory Avoidance and Low Registration patterns and with lower rates of Sensation Seeking (Serafini et al, 2017).…”
Section: Sensory Processing In Healthy Adultssupporting
confidence: 74%
“…In contrast, a Sensation Seeking pattern on the AASP tends to correlate with more adaptive behaviour, such as higher positive affect (Engel-Yeger and Dunn, 2011a) and lower sleep disturbances (Engel-Yeger and Shochat, 2012). Correlates of SPP in healthy adults show continuity with similar studies in people with affective and anxiety disorders, which have shown that such disorders correspond with higher rates of Sensory Sensitivity, Sensory Avoidance and Low Registration patterns and with lower rates of Sensation Seeking (Serafini et al, 2017).…”
Section: Sensory Processing In Healthy Adultssupporting
confidence: 74%
“…In addition to the emotional problems, sensorimotor abnormalities are often present in depression 69 . Clinical data indicate that patients with major depression have decreased volume and surface area of somatosensory cortex and abnormal sensory processing 70 , 71 . Our study examines the cellular underpinning of sensory alterations caused by psychological stress in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized increased insular cortex activity among euthymic patients to be related to impaired sensory integration as well as processing present experiences [ 55 ]. Noteworthy, the aforementioned abilities are thought to be associated with the duration of episodes of depression and mania [ 56 ]. In our study, typical band ALFF analysis revealed increased activity in the left insula.…”
Section: Discussionmentioning
confidence: 99%